Perkembangan Sosial Emosional Anak Usia Dini Melalui Metode Bernyanyi di Raudhatul Athfal Roihanul Jannah - Rosila Rosila; Mukhlis Mukhlis; Sartika Dewi Harahap (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
Rosila, NIM: 20030033, "Early Childhood Social Emotional Development Through the Singing Method in Raudhatul Athfal Roihanul Jannah." This research aims to analyze the social emotional development of early childhood through the singing method. Social emotional development is an important aspect in early childhood education, which is characterized by the ability to interact, socialize and be responsible. The research method used is descriptive qualitative with research subjects being teachers and students. Data was collected through observation, interviews and documentation. The research results show that the singing method is effective in improving children's social emotional development. Children learn to interact with peers, express emotions, and build self-confidence. This research is in line with Erikson's theory which emphasizes the importance of social interaction in child development. The steps in the singing method include selecting an appropriate song, using a tone that is easy to understand, introducing the song, and joint demonstration. Singing activities involve physical activity which makes learning more fun and interactive. This conclusion shows that the singing method is not only fun, but also contributes positively to the social emotional development of early childhood at RA Roihanul Jannah.